OPTIMAL PORTFOLIO FORMATION USING SINGLE INDEX MODEL OF LQ45 STOCKS IN INDONESIA STOCK EXCHANGE FOR 2021-2024 PERIOD - Sari, Ida Ayu Artha Widya; Suadmaya, Ida Bagus; Prameswara, I Gusti Agung Bagus Putra; Nandini, I Gusti Ayu Agung Nararatna Mirah; Putra, I Putu Agus Aditya Pramana; Astuti, Ni Kadek Adi; Kristina, I Gusti Agung Rai; Adibaswara, Made Mas Ananda; Adhitama, Sang Putu Krisnanda (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
The research determines the best portfolio composition using the Single Index Model (SIM) on stocks listed in the LQ45 index at the Indonesia Stock Exchange (IDX) for the 2021-2024 period. 45 stocks that are part of the LQ45 index were evaluated, based on their return, risk, and beta. The Single Index Model was used to choose stocks for the best portfolio based on their Excess Return to Beta (ERB) values compared to a cut-off point. The results show that from 45 stocks analyzed, 10 stocks formed the best portfolio with ADRO having the biggest allocation (75.37%), followed by ITMG (7.94%) and PGAS (4.34%). The mining sector was the biggest in the portfolio, showing it had the best risk-return during the study period. The optimal portfolio gave an expected yearly return of 64.84% with a risk level of 9.76%, and a Sharpe ratio of 6.13, showing very good risk-adjusted performance compared to the market. This research adds to the growing literature on portfolio optimization strategies in emerging markets, especially for Indonesian investors who want to maximize returns while managing investment risks in the IDX.